1988
DOI: 10.1113/jphysiol.1988.sp017121
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of isoprenaline‐ and forskolin‐induced depolarization of single guinea‐pig ventricular myocytes.

Abstract: SUMMARY1. Isoprenaline (10 nM to 1 /M) and forskolin (06-100 /M) depolarized single guinea-pig myocytes studied in vitro. Under voltage clamp both agents caused an inward current to flow.2. These effects were abolished by propranolol (100 nM) and the /,1-antagonist metoprolol (100-200 nM), but not by the fl2-antagonist salbutamol (1 ,FM).3. The interaction of isoprenaline with forskolin, caffeine or isobutylmethylxanthine (IBMX) on current amplitude was as expected if all of these drugs were causing inward cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
65
2

Year Published

1988
1988
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 37 publications
11
65
2
Order By: Relevance
“…The observed hyperpolarization of the membrane potential, V., by isoprenaline in skeletal muscle fibres, has been attributed to stimulation of the Na+-K+-pump by the cyclic AMPdependent cascade (Clausen, 1986;Li & Sperelakis, 1993). From the literature on cardiac tissue however, a more complex picture emerges comprising influences on V. by the stimulation of the Na+-K+-pump (D1silets & Baumgarten, 1986), K+-conductance (Gadsby, 1983;Boyden et al, 1983a), Na+-conductance (Egan et al, 1988), Ca2+-conductance (Tsien et al, 1986) or Cl--conductance (Harvey & Hume, 1989;Ehara & Ishihara, 1990;Nakaya et al, 1990). Also combinations of these effects have been proposed (Encina et al, 1988;Harvey et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The observed hyperpolarization of the membrane potential, V., by isoprenaline in skeletal muscle fibres, has been attributed to stimulation of the Na+-K+-pump by the cyclic AMPdependent cascade (Clausen, 1986;Li & Sperelakis, 1993). From the literature on cardiac tissue however, a more complex picture emerges comprising influences on V. by the stimulation of the Na+-K+-pump (D1silets & Baumgarten, 1986), K+-conductance (Gadsby, 1983;Boyden et al, 1983a), Na+-conductance (Egan et al, 1988), Ca2+-conductance (Tsien et al, 1986) or Cl--conductance (Harvey & Hume, 1989;Ehara & Ishihara, 1990;Nakaya et al, 1990). Also combinations of these effects have been proposed (Encina et al, 1988;Harvey et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that adenosine antagonism of catecholamine stimulated increases in ICa resulted from effects on intracellular cyclic AMP levels (Lerman & Belardinelli, 1990). These actions of adenosine are mediated through adenosine Al receptors coupled to the catalytic subunit of adenylyl cyclase through a pertussis toxin-sensitive guanine nucleotide binding regulatory (Ga) protein (Belardinelli & Pelleg, 1990 (Egan et al, 1988;Boachie-Ansah et al, 1993). It has been suggested that activation of catecholamine induced currents could generate an ectopic ventricular focus leading to tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that activation of catecholamine induced currents could generate an ectopic ventricular focus leading to tachycardia. If more than one focus were activated asynchronously then the rhythm could become chaotic and might precipitate ventricular fibrillation (Egan et al, 1988). Accordingly, subcutaneous administration of isoprenaline was used to facilitate ventricular fibrillation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of potentially important C1-currents have been described in the heart, and they are suggested to play pathophysiological roles by modulating the excitability of cardiac myocyte [1][2][3][4][5][6][7][8][9]. Membrane depolarization induced by a PKAactivated C1-current may result in development of severe arrhythmias associated with acute myocardial infarction [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane depolarization induced by a PKAactivated C1-current may result in development of severe arrhythmias associated with acute myocardial infarction [1][2][3]. A swelling-induced C1-current contributes to the pacemaker potential in sino-atrial nodal cells, and activation of this current results in acceleration of cardiac heart rate [7,8].…”
Section: Introductionmentioning
confidence: 99%